Empyema thoracis in children: A 5-year experience in a Tertiary Care Institute - Kartik Chandra Mandal; Gobinda Mandal; Pankaj Halder; Dipanwita Mitra; Bidyut Debnath; Mala Bhattacharya (Wolters Kluwer Medknow Publications, 2019)
Objective: Empyema thoracis (ET) in children is a disease of significant morbidity and mortality. In the event of failure to resolute following intercostal chest tube drainage (ICD), thoracotomy decortication (TDC) remains the treatment of choice. We have reviewed the outcome of management of 96 cases of ET with the intent to establish the scope of ICD as primary form of the management. Materials and Methods: This is a retrospective study of 96 patients of ET who were managed in pediatric surgery department over a period of 5 years (April 2013 - March 2018). Ninety-six patients at a single center met inclusion criteria for having ET and underwent ICD. We excluded the cases where video-assisted thoracoscopic surgery was provided as primary treatment. The patients were categorized into complicated and uncomplicated groups. Those with pyopneumothorax, encysted empyema, multiloculated empyema, and bilateral ET were assigned as complicated group. There were two treatment groups: (I) those responded with ICD alone (II) those with ICD followed by TDC. Results: All 96 cases received ICD as primary management. There were 54 uncomplicated cases and 42 complicated cases. Out of 42 complicated cases, 26 patients recovered with ICD alone and 16 patients needed TDC. A total of 80 (83.33%) patients (54 uncomplicated ± 26 complicated) recovered with ICD alone. Significant complications were encountered in follow-up of patients who underwent delayed thoracotomy in the form of overriding of the ribs (n = 3) and postoperative air leak (n = 4). There was no mortality in our series. Conclusion: Early initiation of management of ET with intercostal tube drainage is simple, safe, effective even in complicated cases, and has less complications. Thoracotomy with decortication should be reserved for ICD failure cases.